The Resource-Based View as a Developmental Growth Process: Evidence From the Deregulated Trucking Industry - Pettus, Michael L. (Academy of Management Journal, 2001)
This paper develops a resource-based perspective for predicting the sequencing of a firm's resources that best provides for firm growth. The sequencing that generated the highest firm growth combines a Penrosian (1959) perspective with the more recent resource-based literature. This resource development path may be generalizable to other industries, such as airlines, telecommunications, and railroads, that have been deregulated.